Analisa Neraca Panas Cooler pada Pembuatan Magnesium Klorida dengan Proses Netralisasi - Wulandari, Putri Oktavia; Zulaikha, Devie Mirza; Fadilah, Siti Nur; Ningsih, Erlinda (Prosiding Seminar Nasional Sains dan Teknologi Terapan, 2024)
Indonesia is a maritime country that has many natural resources on land and at sea. One of my natural sources that has not been utilized optimally is salt. Magnesium chloride (MgCl2) is a salt that can not be produced because the supply of raw materials for the magnesium chloride (MgCl2) industry has not been resolved. Magnesium chloride (MgCl2) is a compound that is included in the salt compound. Magnesium chloride production is usually used for the pulp, textile and pharmaceutical industries. The magnesium chloride compound is produced through a neutralization reaction between magnesium hydroxide and hydrochloric acid. The product of this reaction is concentrated in an evaporator, then cooled in a cooler. The cooling process in the cooler is an important stage, in this case to reduce the load on the crystallizer. Through data processing in the heat balance calculation process in the cooler, it was found that the heat of the air entering the system was 488,180,452 kJ. The heat of the air coming out is 142,858,499 kJ. The heat absorbed by the cooling water is 345,321, 953, so the total energy in the cooling water is 488,180,452 kJ.